Evaluation of gynoecious cucumber (Cucumis sativus) hybrids for early-summer greenhouse production in western Indian arid plains - KUMAR, PRADEEP; KHAPTE, P S; SAXENA, ANURAG; KUMAR, PRAVEEN (The Indian Journal of Agricultural Sciences, 2019)
A great stride is witnessed in area expansion under protected cultivation, particularly in arid-western parts of India, where cucumber (Cucumis sativus L.) is a predominant greenhouse crop. The early-summer crop of cucumber is highly remunerative owing to high prevailing market price. In current study, efforts were made to select suitable greenhouse cucumber hybrids for early season harvest under western Indian arid plains. Growth, yield and commercial quality traits of seven commercial gynoecious and parthenocarpic (seedless) cucumber hybrids were studied under greenhouse condition during 2015-16. Among the hybrids evaluated for early summer greenhouse production, Terminator was more precocious for fruit harvest (36 days after transplanting) followed by Rica and Dinamik. The per plant fruit yield was highest in Ekron (5.3 kg) followed by Terminator (4.2 kg). The vine length, leaf size and leaf dry weight were also found to be highest in Ekron, followed by Terminator. The fruit appearance, taste and texture, and overall consumer’s acceptability were also determined, which were found better in Rica, Terminator and Dinamik. Despite exhibiting highest production related traits, Ekron measured least score for sensory parameters, especially the fruit appearance due to presence of rudimentary spines on skin, and also the taste. Fruit pericarp thickness and dry matter content were significantly higher in Ekron but the values were at par with that recorded for Terminator and a few other hybrids. The character association analysis reveals that per plant fruit yield had significant positive correlation with vine length, leaf size, foliar (stem+leaf) dry mass and mean fruit weight. Based on targeted characters for earliness, fruit yield and commercial quality of evaluated hybrids, it is concluded that Terminator followed by Rica were highly suitable for early summer production under protected condition in western arid plains of India.